P201 A 15 year retrospective study of outcomes in paediatric tuberculosis disease in a large tertiary centre. (12th November 2019) - Dominiak, K; Turnbull, L; Anderson, R; Hough, S; Wilcock, A; Bhowmik, S; Child, F; Bell, C
Abstract : Background: Incidence rates of Tuberculosis (TB) in the United Kingdom (UK) are amongst the highest in Western Europe (9.2 cases per 100000 population). 1 Despite this there is little data on the clinical burden of TB disease in children and few reports of clinical outcomes for this population. We present outcome data from a 15-year study performed in a large tertiary children's hospital in one of the areas with the highest UK incidence of TB. Method: A retrospective analysis of children ≤16 years identified by pre-entry screening, contact-tracing or by direct referral to TB services between 2003–2017. Information regarding referral type, patient demographic, symptomatology, diagnostics, treatments, side-effects and clinical outcome were gathered from electronic and paper records. Results: On average we investigate 421 children for TB each year. Over this 15 year period we diagnosed 278 children with active TB. Most had Pulmonary TB. 46% of children were referred because they were symptomatic, 51.4% because of a TB contact (17.6% symptomatic) and 2.5% from new-entrant screening. TB was most prevalent in 12–16 year olds (35.5%). Investigations performed varied: Tuberculin skin test (TST) was positive in 89.5% of children and Gamma-Interferon in 74%. 70.2% of TST positive children had a positive Gamma-Interferon result. Microbiology samples were sent in 55.9% cases. 41.9% had at least one positive sample. 78% completed treatment within the designated timeframe. 31 children needed treatment extending due to compliance or persistent disease. 11 children had isoniazid-resistance and 3 had multidrug-resistant TB (MDRTB) requiring alternative regimes. 28% experienced treatment side-effects, including hepatic-impairment and visual disturbance. Following treatment completion 74% of children were discharged with no residual Chest X-ray changes. Eight children developed Bronchiectasis, six respiratory complications not classified as bronchiectasis and one with previous miliary isoniazid-resistant TB re-presented with seizures and died from TB meningitis. Conclusion: This study suggests most children with TB make a complete recovery. We found complications more likely in symptomatic culture positive children possibly representing more virulent disease. This highlights the importance of having a low investigating threshold for children presenting with symptoms suggestive of TB. Treatment side-effects occur rarely but can be life-threatening. Reference: https://www.gov.uk/government/news/tuberculosis-rates-in-england-hit-lowest-recorded-levels.